2017
DOI: 10.1155/2017/9675469
|View full text |Cite
|
Sign up to set email alerts
|

Natural Food Additives and Preservatives for Fish-Paste Products: A Review of the Past, Present, and Future States of Research

Abstract: Fish-paste products, also known as fish cakes or surimi-based products, are worldwide favorites. Surimi, a wet protein concentrate of fish muscle, is used as an intermediate raw material to produce surimi seafood. The flavor, texture, taste, shelf-life, and market value of surimi-based products depend on the source of the fish meat, type of applied heat treatment, and additives used to prepare the surimi. While preparing surimi with chemical additives, several problems have been observed, such as a lack of uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 146 publications
(185 reference statements)
1
33
0
Order By: Relevance
“…() reported similar results where superheated steam of AMPS in combination with water‐soluble chitosan prevented bacterial contamination during the frozen storage. However, the smoke of sawdust having plenty of natural volatile compounds with antioxidant properties might add one more attribute here to prevent TBC (Bashir et al., ; Goulas & Kontominas, ; Guillén & Errecalde, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…() reported similar results where superheated steam of AMPS in combination with water‐soluble chitosan prevented bacterial contamination during the frozen storage. However, the smoke of sawdust having plenty of natural volatile compounds with antioxidant properties might add one more attribute here to prevent TBC (Bashir et al., ; Goulas & Kontominas, ; Guillén & Errecalde, ).…”
Section: Resultsmentioning
confidence: 99%
“…Chen, Wu, and Pan (2015) reported that browning occurred during freezing conditions as a result of decreased sensory quality and market value of the pen shell items. The uses of chemical food additives or attractants in the extension of shelf life has been widely studied (Bashir, Kim, An, Sohn, & Choi, 2017). Moreover, chitosan combined with glutathione was found to have preserving effects on adductor muscle of the pen shell while keeping at frozen conditions (Chen et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is done by releasing incomplete burning smoke from wood or sawdust and letting the volatile chemical compounds in the smoke enhance the aroma of the processed food while inhibiting the bacterial growth on its surface and in the flesh. Factors that affect the effectiveness of smoking treatment are the type of wood, type of volatile compound, and burning temperature [17][18][19]. Smoked food has special flavor and color that can improve the sensory characteristics and the commercial value of a food product [20].…”
Section: Introductionmentioning
confidence: 99%
“…Fish is crushed whole without heading and gutting, and fillet rinsing, therefore, such preservatives as microorganism inhibitors (e.g. potassium sorbate) can be used (Bashir et al, 2017). Structure stabilizers and fillers of plant origin allow to stabilise low viscous consistency of emulsified fish forcemeat from sprats.…”
Section: Development Of Structured Fish Forcemeatmentioning
confidence: 99%